PELATIHAN PENGENDALIAN KREDIT MACET DI KOPERASI BMT TRANS MEKAR SARI MANDIRI KABUPATEN TANJUNG LAGO KABUPATEN BANYUASIN - Agustinus Supriyanto; Santi Octaviani; Rikkie Dekas (LPPM ITB AAS Indonesia Surakarta, 2022)
The risk of bad credit is one of the crucial things for cooperatives, errors in determining the amount of credit given to members will increase the potential for bad loans. This will be very detrimental, therefore in determining credit policy, management needs to know the factors that influence the risk of bad credit. This service aims to provide input in the internal control system in relation to loan services (financing). This service activity was carried out face-to-face which was attended by 27 participants consisting of administrators, supervisors, management and group leaders, at the BMT Trans Mekar Sari Mandiri Consumer Cooperative. The implementation went well and smoothly according to the plan, while the method used was listening to the formulation of the problem, then giving presentations and discussions according to the problems at hand. Participants understand that the joint responsibility method is very helpful and reduces the risk of bad credit. Keywords: Mentoring, Bad Credit, Member Education